Prevalence, risk and protective factors of substance use amongst adolescents living in peri‐urban communities in Abuja, Nigeria - Shuaibu, Hassana Ojonuba; Abdul Rahman, Haliza; Mohd Zulkefli, Nor Afiah (John Wiley & Sons, 2023)
Adolescents living in peri-urban communities are more vulnerable to risky behaviours such as substance use. This was a cross-sectional study carried out to determine the prevalence, risk and protective factors of adolescent substance use in periurban communities in Abuja. Data on lifetime and current substance use were collected using the Youth Risk Behaviour Survey Instrument. Data on risk and protective factors of adolescent substance use, based on the Problem Behaviour Theory, were also collected. Using the SPSS software, descriptive analysis was conducted to summarise the data. Bivariate analysis was conducted using chi-square and independent t-tests, and multivariate analysis was conducted using logistic regression. A p-value of less than 0.05 was considered statistically significant. The prevalence of lifetime substance use was 22.8, whilst current substance use was 18.5. The consumption of mixed drinks was the most currently used form substance at 8.1, followed by alcohol (5.7) and shisha (4.7). Multivariate analysis showed that self-esteem (0.007), delinquency (p < 0.001) and parent alcohol use (p = 0.045) were independently associated with adolescent substance use. There is a high prevalence of substance use amongst adolescents living in peri-urban communities in Abuja, Nigeria, as well as a new pattern of substance use consumption. The findings showed that some risk factors identified by the problem behaviour theory were independently associated with adolescent substance use, whilst the protective factors were not. There is a dire need for adolescent substance use interventions in periurban communities that addresses certain risk factors.